ASOSIASI KADAR YKL-40 SERUM DENGAN PENYEMPITAN CELAH SENDIPADA OSTEOARTRITIS LUTUT SIMPTOMATIS - Irawanto, Farid; -, Arianti; -, Yuliasih; Soeroso, Juwono (journal of internal medicine, 2012)
Osteoarthritis (OA) is the leading cause of chronic disability in population. Because individuals with early stages of thedisease are often asymptomatic, a biomarker of early OA may be useful. YKL-40, a major secretory protein of humanchonrocytes and synovial cells, is increased in the serum and synovial uid of individuals with joint or cartilage disease.This study evaluated serum levels YKL-40 in patients with knee OA and its relation with join space narrowing.YKL-40 wereassayed in serum samples from 44 patients (36 women, 8 men, mean age 50 ? 60) with symptomatic OA of the knee joint.YKL-40 assayed by immunoassay and joint space narrowing by ultrasound. OA severity was assessed by the measurementdegree of joint space width with ultrasound. Statistical analysis was perfomed to determine association between serummarker and radiological join space width.The mean (standard error) YKL-40 level was 82.66 ng/ml in patients with knee OA.The serum levels of YKL-40 and joint space narrowing were signi!cantly correlated (Spearman test r = 0.769; p < 0.01).inpatients with symptomatic knee OA. Serum YKL-40 may be a marker of joint inflammation in symptomatic OA.